Assesstment of Working Capital in the Plantation Sector Based on ROI, ROA and ROE Management Analysis - Haryanto, Lenawati; Mastina, Fransiska Rosa (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The purpose of this study was to analyze Working Capital Management to assess ROI, ROA, and ROE in the Plantation Sector. This study consists of three independent variables consisting of ROI, ROA, and ROE, and one dependent variable, namely Working Capital. In this study there were 27 companies that met the criteria from a total of 32 observations with the object of research in the plantation sector plantation companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2022. the results of this study indicate that the ROI variable has a negative effect on working capital. ROA variable has a positive effect on working capital. ROE variable has a positive effect on working capital. This research can also be taken into consideration for investors and shareholders to be more careful in receiving financial statement information provided by the company in making decisions.